Assessing Competence in Critical Care Echocardiography: Development and Initial Results of an Examination and Certification Processes*. Issue 8 (August 2021) - Panebianco, Nova L.; Mayo, Paul H.; Arntfield, Robert T.; Brown, Sam M.; Diaz-Gomez, Jose; Hernandez, Antonio; Koenig, Seth J.; Noble, Vicki; Sekiguchi, Hiroshi; Subhiyah, Raja G.; Mulvagh, Sharon; Saric, Muhamed; et al.
Abstract : OBJECTIVES: To describe the development and initial results of an examination and certification process assessing competence in critical care echocardiography. DESIGN: A test writing committee of content experts from eight professional societies invested in critical care echocardiography was convened, with the Executive Director representing the National Board of Echocardiography. Using an examination content outline, the writing committee was assigned topics relevant to their areas of expertise. The examination items underwent extensive review, editing, and discussion in several face-to-face meetings supervised by National Board of Medical Examiners editors and psychometricians. A separate certification committee was tasked with establishing criteria required to achieve National Board of Echocardiography certification in critical care echocardiography through detailed review of required supporting material submitted by candidates seeking to fulfill these criteria. SETTING: The writing committee met twice a year in person at the National Board of Medical Examiner office in Philadelphia, PA. SUBJECTS: Physicians enrolled in the examination of Special Competence in Critical Care Electrocardiography (CCEeXAM). MEASUREMENTS AND MAIN RESULTS: A total of 524 physicians sat for the examination, and 426 (81.3%) achieved a passing score. Of the examinees, 41% were anesthesiology trained, 33.2% had pulmonary/critical care background, and the majority had graduated training within the 10 years (91.6%). Most candidates work full-time at an academic hospital (46.9%). CONCLUSIONS: The CCEeXAM is designed to assess a knowledge base that is shared with echocardiologists in addition to that which is unique to critical care. The National Board of Echocardiography certification establishes that the physician has achieved the ability to independently perform and interpret critical care echocardiography at a standard recognized by critical care professional societies encompassing a wide spectrum of backgrounds. The interest shown and the success achieved on the CCEeXAM by practitioners of critical care echocardiography support the standards set by the National Board of Echocardiography for testamur status and certification in this imaging specialty area. Abstract : Supplemental Digital Content is available in the text.